SL-01 Teaching Method and Current Research Interest in Veterinary Anatomy with Special Reference to Bogor Agricultural University - Tutik Wresdiyati (Media Veteriner, 2015)
Teaching and learning methods in the field of Veterinary Anatomy in Indonesia are still using classic methods, such as lectures in class and continued with laboratory practices. To facilitate student centered learning, discussion using some teaching aid materials are used in the laboratory practices. The method continues to be improved from time to time to increase the student interest in the study of Veterinary Anatomy and to assist and facilitate student for a better understanding of the subject ........